Middle-Aged Men’s Traumas and Elusive Freedom in Hanif Kureishi’s Short Stories - Vesna Ukić Košta ([sic])
This paper sets out to explore a notion of freedom that Hanif Kureishi articulates in his short stories, focusing particularly on the collections Love in a Blue Time (1997) and Midnight All Day (1999). Kureishi’s stories almost always narrated from the point of view of a middle-aged man are here analysed in the light of Zygmunt Baumann’s theories of liquid modernity and liquid love. The paper attempts to demonstrate that these men are confined to a sort of a perpetual treadmill of misery. It is argued that most protagonists of his stories are largely unable to manage their lives and relationships, living in a contemporary world that allows individuals to enjoy excesses of freedom and infinite possibilities. Keywords: Hanif Kureishi, short story, middle-aged, freedom, liquid modernity, liquid love, familySomewhere towards the end of Hanif Kureishi’s 1995 novel The Black Album, the main protagonist, twenty-year-old Shahid Hasan, enthusiastically embraces the prospect of breaking free from the constraints of race that heavily determine his identity throughout the narrative: “There was no fixed self; surely our several selves melted and mutated daily? There had to be innumerable ways of being in the world. He would spread himself out, in his work and in love, following his curiosity” (274). A member of second-generation immigrants from India in contemporary Britain, faced with demands of his friends who have turned into religious radicals, he seems able to finally assert himself as an individual unburdened by his non-British origins, which constituted this ‘fixed self’ for much of his life. In a similar vein, in Kureishi’s semi-autobiographical novel The Buddha of Suburbia published five years earlier in 1990, mixed race Karim Amir struggles to come to terms with being “a funny kind of Englishman, a strange breed … emerging from two old histories” (3). In the course of the novel, Karim manages to flee the drab South London suburbia, both literally and metaphorically by constantly (or why not daily) probing his “several selves” in order to find his own way of “being in the world.”